The Quality of Work Environment of Nurses in a Public Hospital in Negros Occidental - Adis, Susan Jane T.; Arnibal, Sheila P. (Philippine Social Science Journal, 2020)
The World Health Organization Regional Office of the Western Pacific’s definition of a healthy workplace is a place where all members work together to achieve a unified vision for the health and well-being of the workers and the community. A healthy work environment is where all members are provided with the physical, psychological, social, and organizational states that protect and promote their health and safety. A positive work environment for nurses has been concisely described as a work environment where nurses are supported to function at the highest scope of clinical practice, working effectively in an interdisciplinary manner with the team of caregivers mobilizing resources quickly. This paper describes the level of quality of the work environment of nurses in a public hospital in Negros Occidental. Likewise, it explores the difference in the level of quality of the work environment when nurses are grouped according to their demographics. Also, it determines the challenges encountered by nurses in their work environment.